Optical Properties of Injection-Molded Polystyrene Scintillators. II. Distribution of Dopants - Martins, J. A. (2003)
The distribution of fluorescing dye solutes in scintillating tiles for the Tilecal/Atlas project is assessed, and a link between the homogeneity of the dopant distribution and the optical yield and nonuniformity is established. The effect of the injection-molding parameters on the dye distribution is also analyzed, as well as the actual dye incorporation into the scintillators. This incorporation has been assessed with a set of experiments performed with laboratory samples with controlled amounts of additives and with samples obtained from injection-molded scintillators. Differential scanning calorimetry has been used to characterize the raw material and to establish a link between the thermophysical properties and the processing conditions, and it is proven to be a quite appropriate technique.